Construction industry and payment discipline in the Czech Republic - Lucie Kureková; Pavlína Hejduková (European Financial and Accounting Journal, 2016)
The paper deals with payment discipline in the building industry in the Czech Republic. The aim of this paper is to identify, compare and evaluate the financial situation of building companies with different payment practices in the Czech Republic in the period 2010 - 2014. The paper uses enterprise and statistical methods. The payment discipline of companies is expressed by a payment index, which is constructed by Bisnode. The results are based on analysis of 1374 companies which are operated in the building industry. The analysis shows that payment habits increase with higher index IN05, Taffler's model, index IN99 and with larger size of the firms. Payment habits of building companies are very good. However, about 2 % of solvent companies have poor payments habits.
Keywords: G31; G32; G33; L74; M21; 650; Bankruptcy models; Companies; Construction industry; Payment discipline; Payment index